(untitled) (Praxis Educativa, 2018)
Presence is less and less related to the location and timing, currently “being” is too to “connect” on the network from anywhere, thus, each publication, acquires characteristics ubiquitous and renewable conferred by technology. Subjects mutating its traditional presentiality of co-habitation and proximity to mixed presentiality, most of times associated to the couple “Offline/ On-line”, considered a continuum without sutures, because of that people and social organizations exist in various dimensions and platforms. This article analyzes the construction of the presence on Facebook of the ”Unidades Educativas del Milenio” (UEM), ecuadorian institutions proposed as a model wich promove teaching talent, quality infrastructure, community participation and integration of Information and Communications Technology (ICT) in learning. Statistics show low participation of UEM in the social network, representation with photos of students and buildings and a larger number of unofficial pages.